2018
DOI: 10.1021/acs.jcim.8b00045
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Cytotoxic Aβ25–35 Peptide to the Dimyristoylphosphatidylcholine Lipid Bilayer

Abstract: Aβ25-35 is a short, cytotoxic, and naturally occurring fragment of the Alzheimer's Aβ peptide. To map the molecular mechanism of Aβ25-35 binding to the zwitterionic dimyristoylphosphatidylcholine (DMPC) bilayer, we have performed replica exchange with solute tempering molecular dynamics simulations using all-atom explicit membrane and water models. Consequences of sequence truncation on the binding mechanism have been measured by utilizing as a control our previous simulations probing binding of the longer pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(107 citation statements)
references
References 56 publications
10
97
0
Order By: Relevance
“…The change in hyperfine splitting A + (Aβ) - A + (L) of 16-DSE of about 30 mG (Figure 5 – diamonds and triangles) in all four phospholipids unambiguously indicate that there is a population of Aβ(25–35) deep in the bilayer. This result agrees with the findings of Mason et al(Mason et al, 1996) who observed by X-ray diffraction that Aβ(25–53) inserts into the bilayer hydrocarbon core of 1-Palmitoyl-2-oleoyl phosphatidylcholine (POPC) vesicles, as well as with the results of Dante et al(Dante et al, 2002), Dies et al(Dies et al, 2014) Labbe et al(Labbé et al, 2013) and Smith et al(Smith and Klimov, 2018) which are discussed above. The circle and square symbols at the lower temperatures in Figure 5 point to the second population of Aβ(25–35).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The change in hyperfine splitting A + (Aβ) - A + (L) of 16-DSE of about 30 mG (Figure 5 – diamonds and triangles) in all four phospholipids unambiguously indicate that there is a population of Aβ(25–35) deep in the bilayer. This result agrees with the findings of Mason et al(Mason et al, 1996) who observed by X-ray diffraction that Aβ(25–53) inserts into the bilayer hydrocarbon core of 1-Palmitoyl-2-oleoyl phosphatidylcholine (POPC) vesicles, as well as with the results of Dante et al(Dante et al, 2002), Dies et al(Dies et al, 2014) Labbe et al(Labbé et al, 2013) and Smith et al(Smith and Klimov, 2018) which are discussed above. The circle and square symbols at the lower temperatures in Figure 5 point to the second population of Aβ(25–35).…”
Section: Resultssupporting
confidence: 92%
“…The circle and square symbols at the lower temperatures in Figure 5 point to the second population of Aβ(25–35). The weak effect Aβ(25–35) on the surface of the vesicles can be explained by the MD simulation results of Smith et al(Smith and Klimov, 2018) in which the authors suggest that the surface-bound peptides point away from the vesicle surface. The temperature behavior of A + (Aβ) - A + (L) of TP (blue and red symbols in Figure 5) supports this interpretation, since the peptide conformation very likely becomes more extended with increasing temperature, which causes the decrease in the magnitude of A + (Aβ) - A + (L), as observed in Figure 5.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations